Submarine cable
The water treeization and dielectric loss of wet design submarine cables in brine environments is solved by using blends of LDPE and polar copolymers as well as carbon black and peroxides in submarine cables. Problem, achieving efficient cable performance and environmentally friendly material use.
Patent Information
- Application Number
- CN202380043405.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-12
- Filing Date
- 2023-04-12
- Publication Date
- 2025-01-10
AI Technical Summary
Existing wet-designed submarine cables face water tree formation and dielectric loss problems in salt water environments, resulting in electrical breakdown and electrical failures, and traditional moisture-proof layers increase material costs and have negative impacts on the environment.
A blend of low-density polyethylene (LDPE) and polar copolymers is used as an insulating layer, combining carbon black and peroxide to form a crosslinkable submarine cable core to improve water tree resistance and reduce dielectric loss.
In a salt water environment, the cable's water tree resistance and dielectric loss performance are significantly improved, the cable's service life is extended, the material cost is reduced, and environmental pollution is reduced.
Smart Images

Figure BDA0005157091280000301 
Figure BDA0005157091280000302
Abstract
Description
[0001] The present invention relates to a wet-type cable for use in a saltwater environment (hereinafter referred to as a submarine cable), in particular to a wet-type submarine power cable operating at high voltage, i.e., a submarine power cable, comprising at least one cable core, the cable core comprising an insulation layer, in which a blend of polyolefin and polar copolymer, in particular a blend of low-density polyethylene (LDPE) and polar copolymer is used to achieve water tree retardation. The present invention also relates to a method for preparing such a submarine cable and the use of such a submarine cable in a saltwater environment (e.g., a submarine environment). Background Art
[0002] Sustainable development, defined as "development that meets the needs of the present without compromising the ability of future generations to meet their own needs", is a central topic around the world. In addition, as a technology supplier to the power industry, the cable industry is supporting many of the changes the industry is making to provide a more sustainable power system.
[0003] Power cables can play an important role in sustainable development, for example by enabling the integration of remote offshore renewable energy sources through submarine power cable technology. Submarine cables are used in a variety of scenarios, such as offshore renewable energy onshore projects, such as wind farms or wave and tidal systems, island power supply, autonomous grid connection, offshore platform power supply, short-distance crossing (e.g. power transmission across rivers, canals, straits, fjords, bays or lakes). Typically, these submarine cable systems transmit power at high voltage (HV).
[0004] Taking sustainability into consideration, it is also necessary to design materials used in power cables (including submarine power cables), consider the sustainable development performance of the materials, and focus on how to conveniently dispose of the cables when they reach their end of life (EOL) to promote the development of a circular economy.
[0005] A standard power cable comprises at least one cable core. Each cable core comprises a conductor, which is in turn surrounded by an inner semiconductive layer (also called conductor shield), an insulating layer and an outer semiconductive layer (also called insulating shield). The cable may also be provided with additional components and layers, such as a sheath layer, which is well known in the art.
[0006] When using cables underwater, it is well known to coat the cables with a moisture barrier, usually a metal one, to protect the cables from problems caused by water ingress. We call this a dry cable design. The moisture barrier prevents water from entering the cable, but it significantly increases the raw material cost of the cable and is also expensive to use. In addition, conventional moisture barriers are usually made of lead, which has a significant impact on the environment.
[0007] In contrast to the dry design we have the so-called wet design or wet cable construction, which is defined as a cable construction in which no moisture barrier is present. Thus, this design has no moisture barrier, in particular no extruded metal moisture barrier. The terms "dry" and "wet" design are well known in the art and are also discussed in Cigre TB722.
[0008] Wet-design cable construction allows water or moisture to penetrate into the cable core. This allows for a "simpler" cable design in which at least one layer and the corresponding manufacturing steps are omitted, thereby reducing material consumption and improving the sustainability performance of the cable design. At the same time, eliminating the moisture barrier (usually an extruded metal sheet) also facilitates the treatment of the cable at the end of its service life and thus improves sustainability performance.
[0009] However, allowing water to penetrate the interior of power cables is no small matter, and it is well known that the service life of insulated cables is often shortened when they are installed in environments where the polymer insulation is exposed to water, such as underground, in places with high humidity or underwater.
[0010] The combination of electric field and water can lead to water tree degradation of insulating materials due to the effects of inhomogeneities, microcavities and impurities present in the insulating materials. Water tree structures cause local damage to the insulating layer, thereby reducing the electrical breakdown strength. If the growth of water trees triggers electrical trees, it may eventually lead to electrical breakdown or electrical failure.
[0011] Therefore, in wet-design cables, care must be taken to maximize the water tree resistance (WTR) properties of the cable insulation, and these cables must undergo rigorous testing, including wet aging testing, to demonstrate that the cables have adequate water resistance.
[0012] One proven WTR technology is the so-called "polymer WTR", i.e. the addition of a polar copolymer to an LDPE-type matrix. WTR solutions are well known in the art and described in various publications.
[0013] In EP1731566 it is taught that the use of an unsaturated polyolefin having a specific vinyl content in combination with a polar copolymer can improve the wet aging properties.
[0014] WO2010 / 112333 describes a cable comprising a conductor surrounded by a semiconducting layer and an insulating layer, wherein the semiconducting layer consists of a composition (A) comprising a polar copolymer (a) and carbon black, and the insulating layer consists of a composition (B) comprising a polar copolymer, wherein the difference between the melting temperature of the polar copolymer (a) and the melting temperature Tm(b2) of the polar copolymer (b2) is less than 25°C.
[0015] WO 85 / 05216 describes an insulation composition consisting of polyethylene and 10 to 40% by weight of a (meth)acrylate polymer, such as ethylene butyl acrylate (EBA).
[0016] JP H08 319381 illustrates some blends based on ethylene methyl acrylate (EMA) and LDPE and test sheets made therefrom, which are subjected to a water tree test in a very strong salt solution (2 mol / L).
[0017] Since submarine power cables are exposed to very harsh conditions, such as the potential corrosiveness of seawater, and operate at higher voltages, typically 33 kV, 66 kV and above 66 kV (RMS value of the voltage between any two conductors or phases in a three-phase cable), the inventors are particularly interested in the wet aging performance of submarine power cables operating at these higher voltages in a saltwater environment (as described in Cigré TB722).
[0018] As observed in small-scale tests, salt water or seawater also tends to exacerbate water treeing issues in cables, so designing submarine cables for exposure to salt water is challenging. In addition to sodium chloride, salt water can contain magnesium ions, calcium ions, potassium ions, sulfate ions, etc. These dissolved salts can have an impact on water tree formation in wet-design cables. Seawater, such as salt water, is a more aggressive environment than, for example, fresh water. Therefore, it does not mean that materials that can operate in fresh water environments can withstand exposure to seawater.
[0019] Furthermore, as mentioned above, submarine power cables usually operate at higher voltages. This places higher demands on the dielectric loss level of the selected insulation material. Dielectric losses are linearly proportional to tanδ and are preferably kept as low as possible for technical and economic reasons and for sustainable development considerations. Low losses mean that only a small amount of the transmitted electrical energy is lost as heat energy within the cable core insulation. These losses would mean economic losses for the power line operator. Low losses also reduce the risk of thermal runaway, i.e. an unstable situation where the temperature of the insulation increases due to tanδ. When the temperature increases, tanδ will generally also increase. This will further increase the dielectric losses and thus the temperature. The result will be dielectric failure of the cable.
[0020] As mentioned above, wet design cables typically use WTR solutions such as polymer WTR to exhibit adequate water resistance. However, a disadvantage of polymer WTR solutions is that the dielectric loss measured by tan δ may be increased compared to the dielectric loss of dry design polymer solutions typically used for high voltage (HV) applications.
[0021] Therefore, it is necessary to identify a submarine cable core material system (i.e., the material combination of the insulation layer and the semi-conductive layer of the submarine cable core) that can operate in a high-pressure salt water environment and balance the salt water wet aging performance and the dielectric loss level measured by tan δ, while maintaining good sustainable performance.
[0022] Johansson et al. discussed wet-designed cables, i.e. the effects of subsea conditions on the long-term performance of AC XLPE cables, at the 8th International Conference on Insulated Power Cables, Jicable'11, June 19-23, 2011, Versailles, France. The tested cables used a high performance water-tree resistant copolymer XLPE.
[0023] In a presentation titled “Full scale wet age testing of XLPE insulated power cables in salt water,” presented at the Jicable ’19 conference held in Paris on June 23-27, 2019, Featherstone et al. described salt water testing of wet-design XLPE cables.
[0024] The present invention is based on the surprising discovery that the above needs can be met by an insulation layer for wet-design submarine cables and cable cores, in particular wet-design submarine power cables and cable cores, comprising the following combination: (i) a LDPE homopolymer or LDPE copolymer with a polyunsaturated comonomer, and (ii) a copolymer comprising a small amount of polar monomer units, for example, an amount of polar monomer units of 1 to 150 micromoles (1×10 mol) per gram in the total polymer fraction of the composition. -6 Up to 150×10 -6 mol), which balances salt water wet aging performance with dielectric loss as measured by tan δ.
[0025] The combination of specific polymers in the insulating and semiconducting layers defined herein that are resistant to dielectric breakdown in a saline environment while maintaining acceptable dielectric losses or tan delta is novel. Summary of the invention
[0026] Viewed from one aspect, the invention provides a submarine cable core, for example for transmitting power in a saltwater environment, such as in the sea or on the seafloor;
[0027] The cable core comprises a conductor which is surrounded in sequence at least by an inner semiconducting layer, an insulating layer and an outer semiconducting layer;
[0028] Wherein, the insulating layer comprises:
[0029] (i) a low density polyethylene homopolymer or a low density polyethylene copolymer comprising at least one polyunsaturated comonomer and optionally one or more other comonomers; and
[0030] (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate,
[0031] Wherein, the amount of the polar monomer unit in the insulating layer is 1 to 150 micromoles per gram based on the total amount of the polymer in the insulating layer.
[0032] Viewed from another aspect, the invention provides a submarine cable core, such as for use in transmitting power in a saltwater environment, such as in the sea or on the seafloor;
[0033] The cable core comprises a conductor which is surrounded in sequence at least by an inner semiconducting layer, an insulating layer and an outer semiconducting layer;
[0034] Wherein, the insulating layer comprises:
[0035] (i) a low density polyethylene homopolymer or a low density polyethylene copolymer comprising at least one polyunsaturated comonomer and optionally one or more other comonomers; and
[0036] (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate,
[0037] wherein the amount of the polar monomer unit in the insulating layer is 1 to 150 micromoles per gram based on the total amount of the polymer in the insulating layer; and
[0038] Wherein, the inner semiconductive layer and the outer semiconductive layer independently comprise:
[0039] (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate; and
[0040] (b) Carbon black.
[0041] Viewed from another aspect, the present invention provides a use of a submarine cable core, the cable core comprising a conductor surrounded in sequence at least by an inner semiconducting layer, an insulating layer and an outer semiconducting layer;
[0042] Wherein, the insulating layer comprises:
[0043] (i) a low density polyethylene homopolymer or a low density polyethylene copolymer comprising at least one polyunsaturated comonomer and optionally one or more other comonomers; and
[0044] (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate,
[0045] wherein the amount of the polar monomer unit in the insulating layer is 1 to 150 micromoles per gram based on the total amount of the polymer in the insulating layer; and
[0046] Wherein, the inner semiconductive layer and the outer semiconductive layer independently comprise:
[0047] (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate; and
[0048] (b) Carbon black.
[0049] Viewed from one aspect, the present invention provides a submarine cable comprising at least one submarine cable core, preferably at least three submarine cable cores as defined above.
[0050] The submarine cable of the present invention is preferably a wet design submarine cable.
[0051] The submarine cable core of the present invention is cross-linkable or cross-linked. Therefore, in another embodiment, the insulating layer also comprises a cross-linking agent, preferably a peroxide, and is cross-linkable. In another embodiment, the inner semiconductive layer and / or the outer semiconductive layer also comprise a cross-linking agent, preferably a peroxide, and are cross-linkable. In another embodiment, the insulating layer, the inner semiconductive layer and the outer semiconductive layer also comprise a cross-linking agent, preferably a peroxide, and are cross-linkable. When in cross-linking conditions, the cross-linkable submarine cable core can be cross-linked. Peroxide decomposes and produces free radicals, which initiate a cross-linking reaction in the composition. Therefore, after the cross-linking reaction occurs, the peroxide is substantially completely consumed.
[0052] Viewed from another aspect, the invention provides a crosslinked submarine cable core obtainable by crosslinking a crosslinkable submarine cable core as defined above. Viewed from another aspect, the invention provides the use of a crosslinked submarine cable core as defined above, for example in a submarine cable for transmitting power in a saltwater environment, for example in the sea or on the seabed.
[0053] Viewed from another aspect, the invention provides a method for producing a submarine cable core, the submarine cable core comprising a conductor, the conductor being surrounded in sequence at least by an inner semiconducting layer, an insulating layer and an outer semiconducting layer, wherein the method comprises the following steps:
[0054] - extruding (e.g. co-extruding) an inner semiconducting layer, an insulating layer and an outer semiconducting layer on the conductor; and
[0055] - crosslinking one or more of the inner semiconducting layer, the insulating layer and the outer semiconducting layer;
[0056] Wherein, the insulating layer comprises:
[0057] (i) a low density polyethylene homopolymer or a low density polyethylene copolymer comprising at least one polyunsaturated comonomer and optionally one or more other comonomers; and
[0058] (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate,
[0059] wherein the amount of the polar monomer unit in the insulating layer is 1 to 150 micromoles per gram based on the total amount of the polymer in the insulating layer; and
[0060] Wherein, the inner semiconductive layer and the outer semiconductive layer independently comprise:
[0061] (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate; and
[0062] (b) Carbon black. DETAILED DESCRIPTION
[0063] The present invention provides a submarine cable core and a submarine cable for use in a saltwater environment comprising the cable core, such as a crosslinkable submarine cable or a crosslinked submarine cable, such as a crosslinkable or crosslinked submarine power cable, the cable comprising at least one cable core, the cable core comprising a conductor, the conductor being surrounded in sequence at least by an inner semiconductive layer, an insulating layer and an outer semiconductive layer. The present invention also relates to a crosslinked submarine cable, the cable comprising a conductor, the conductor being surrounded by at least an inner semiconductive layer, an insulating layer and an outer semiconductive layer.
[0064] As used herein, in the present specification and claims, the term "brine" or "brine environment" refers to water containing dissolved sodium chloride (NaCl), and the NaCl content is 1.0 wt% or more, preferably 2.0 wt% or more, more preferably 3.0 wt% or more, and at most 10 wt% or less, preferably 8 wt% or less, more preferably 6 wt% or less, relative to the total amount of water.
[0065] As used herein, the term "cable" is intended to mean a cable comprising at least one cable core, optionally two cable cores and preferably three cable cores. As used herein, each "cable core" comprises a conductor surrounded by at least an inner semiconductive layer, an insulating layer and an outer semiconductive layer.
[0066] One or more cable cores in a cable may be surrounded by at least one reinforcement layer and / or armor layer for mechanical protection of the cable. The armor layer may include metal conductors, a braid, a sheath, or a low-loss armor. These variations and cable structures are familiar to those skilled in the art. The armor layer may extend through a portion of the cable.
[0067] The term "AC cable" refers to an alternating current (AC) cable comprising at least three cable cores, each cable core corresponding to one of three phases.
[0068] The term "subsea" is intended to mean located at least partially beneath or in any body of salt water, such as a saltwater lake, sea, ocean, etc., as defined above. For example, a subsea cable refers to a cable that runs at least partially beneath or in any body of salt water.
[0069] In this specification, the term "high voltage" or HV refers to a voltage higher than 33 kV, preferably higher than 36 kV (RMS value of the voltage between any two conductors or phases in a three-phase cable).
[0070] The submarine cable comprising at least one cable core of the present invention preferably adopts a wet design as defined above. Ideally, the submarine cable does not include a moisture barrier to prevent water ingress. Despite the wet design, the submarine cable comprising at least one cable core of the present invention still exhibits excellent anti-water tree performance in a saltwater environment while maintaining acceptable dielectric loss performance. This can be demonstrated by electrical breakdown strength analysis and tan δ measurement of the cable core after wet aging in saltwater, respectively. Therefore, from another perspective, the present invention provides a submarine cable core and a submarine cable having improved electrical breakdown strength in a saltwater environment while maintaining low dielectric loss.
[0071] Some experts consider the presence of a polymer sheath over the outer semiconductive layer to be a "semi-wet" design because the sheath layer limits the water vapor permeation rate. We consider this solution a wet design because the sheath layer is not waterproof or moisture proof.
[0072] Insulation layer
[0073] The submarine cable core of the present invention comprises an insulation layer, the insulation layer comprising:
[0074] (i) a low density polyethylene homopolymer or a low density polyethylene copolymer comprising at least one polyunsaturated comonomer and optionally one or more other comonomers; and
[0075] (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate,
[0076] Wherein, the amount of the polar monomer unit in the insulating layer is 1 to 150 micromoles per gram based on the total amount of the polymer component in the insulating layer.
[0077] Low density polyethylene homopolymer or low density polyethylene copolymer with at least one polyunsaturated comonomer and optionally one or more other comonomers - insulation layer
[0078] Component (i) of the insulation layer is a LDPE homopolymer or a LDPE copolymer with at least one polyunsaturated comonomer and optionally one or more further comonomers. This is referred to herein as LDPE polymer component (i).
[0079] Although the term LDPE is an abbreviation for low-density polyethylene, the term should be understood not to limit the density range, but to cover high-pressure polymerized (HP) polyethylene similar to LDPE. Compared with polyethylene produced in the presence of olefin polymerization catalysts, the term LDPE only describes and distinguishes the properties of HP polyethylene with typical characteristics (such as different branching structure).
[0080] It should be understood that the term "LDPE homopolymer" generally refers to a low density polyethylene polymer consisting essentially of ethylene monomers. Thus, ideally, the LDPE homopolymer contains no comonomers. However, small amounts of comonomers other than ethylene can be tolerated without substantially affecting the properties of the LDPE, since the material is still essentially a homopolymer. In this regard, a small amount of comonomers is understood to be less than 3% by weight, such as less than 1%, less than 0.5%, or less than 0.1% by weight of comonomers other than ethylene, based on the total weight of the LDPE homopolymer.
[0081] Preferably, the LDPE polymer component (i) is a LDPE copolymer with at least one polyunsaturated comonomer.
[0082] In one embodiment, the LDPE polymer component (i) is a LDPE copolymer having at least one polyunsaturated comonomer and optionally one or more other comonomers.
[0083] Preferably, the LDPE copolymer component (i) is a binary copolymer of ethylene and only one polyunsaturated comonomer.
[0084] The polyunsaturated comonomer preferably consists of a straight carbon chain having at least 8 carbon atoms and at least 4 carbon atoms located between non-conjugated double bonds, wherein at least one double bond is located at the terminal. The polyunsaturated comonomer is preferably a diene, such as a diene comprising at least 8 carbon atoms, the first carbon-carbon double bond is located at the terminal and the second carbon-carbon double bond is not conjugated with the first carbon-carbon double bond, such as selected from C8 to C 14The diene of the non-conjugated diene or a mixture thereof is, for example, selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene, 1,13-tetradecadiene or a mixture thereof, for example selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene, 1,13-tetradecadiene.
[0085] If another comonomer is present, it may be C3 to C 10 α-Olefins.
[0086] The LDPE copolymer component (i) preferably comprises 0.001 to 40 wt%, preferably 0.05 to 40 wt%, more preferably 0.05 to 30 wt%, further more preferably 0.10 to 30 wt%, further more preferably 0.10 to 20 wt% of one or more comonomers in total (i.e. all comonomers), based on the total weight of the LDPE copolymer. In one embodiment, the LDPE copolymer comprises 0.05 to 20 wt%, preferably 0.05 to 15 wt%, such as 1.0 to 10 wt%, in particular 0.05 to 5.0 wt%, such as 1.0 to 5.0 wt%, more particularly 0.05 to 3.0 wt%, such as 0.10 to 3.0 wt%.
[0087] The polyunsaturated comonomer content is preferably 0.001 to 10 wt%, preferably 0.01 to 10 wt%, more preferably 0.01 to 5.0 wt%, even more preferably 0.01 to 3.0 wt%, especially 0.01 to 2.0 wt%, more especially 0.1 to 2.0 wt%. In some embodiments, the only comonomer present is a polyunsaturated comonomer.
[0088] The LDPE polymer component (i) is preferably unsaturated. The total amount of carbon-carbon double bonds is preferably more than 0.4 / 1000 carbon atoms, preferably more than 0.5 / 1000 carbon atoms, for example more than 0.6 / 1000 carbon atoms, in particular more than 0.7 / 1000 carbon atoms, for example more than 0.8 / 1000 carbon atoms. The upper limit of the number of carbon-carbon double bonds present in the polyolefin is not limited, and may preferably be less than 5.0 / 1000 carbon atoms, preferably less than 3.0 / 1000 carbon atoms.
[0089] In some embodiments, the total amount of carbon-carbon double bonds derived from vinyl, vinylidene and trans-vinylene (if present) in the LDPE polymer component (i) is higher than 0.40 / 1000 carbon atoms, preferably higher than 0.50 / 1000 carbon atoms, more preferably higher than 0.60 / 1000 carbon atoms, even more preferably higher than 0.70 / 1000 carbon atoms, yet even more preferably 0.75 / 1000 carbon atoms, in particular 0.8 / 1000 carbon atoms. Preferably, the total amount of carbon-carbon double bonds derived from vinyl, vinylidene and trans-vinylene is lower than 5.0 / 1000 carbon atoms, preferably lower than 3.0 / 1000 carbon atoms.
[0090] In some embodiments, the LDPE polymer component (i) contains at least vinyl groups, and the total amount of vinyl groups is preferably higher than 0.05 / 1000 carbon atoms, further more preferably higher than 0.08 / 1000 carbon atoms, and most preferably higher than 0.11 / 1000 carbon atoms. In some embodiments, the LDPE polymer component (i) contains at least vinyl groups, and the total amount of vinyl groups is preferably higher than 0.10 / 1000 carbon atoms, such as higher than 0.15 / 1000 carbon atoms, such as higher than 0.20 / 1000 carbon atoms, more preferably higher than 0.25 / 1000 carbon atoms, especially higher than 0.30 / 1000 carbon atoms, more especially higher than 0.35 / 1000 carbon atoms, most especially higher than 0.40 / 1000 carbon atoms, such as higher than 0.45 / 1000 carbon atoms or 0.50 / 1000 carbon atoms.
[0091] Preferably, the total amount of vinyl groups is less than 4.0 / 1000 carbon atoms. More preferably, the LDPE polymer component (i) contains a total amount of vinyl groups of more than 0.20 / 1000 carbon atoms, even more preferably more than 0.30 / 1000 carbon atoms, and most preferably more than 0.40 vinyl groups / 1000 carbon atoms, such as more than 0.45 vinyl groups / 1000 carbon atoms, before crosslinking.
[0092] It should be understood that in this specification, all amounts or values related to unsaturation, such as vinyl, vinylidene, and trans-vinylene, generally refer to amounts or values determined prior to crosslinking.
[0093] Preferably, the melt flow rate MFR2.16 / 190°C of the LDPE polymer component (i) is from 0.1 to 50 g / 10 min, preferably from 0.3 to 20 g / 10 min, more preferably from 0.3 to 15 g / 10 min, even more preferably from 0.50 to 15 g / 10 min or from 0.60 to 10 g / 10 min, for example from 0.60 to 3.0 g / 10 min. In some embodiments, MFR2 is 0.50 to 8.0 g / 10min, for example 0.60 to 6.0 g / 10min, preferably 0.70 to 5.5 g / 10min, for example 0.80 to 5.0 g / 10min, more preferably 0.90 to 4.75 g / 10min, even more preferably 1.0 to 4.5 g / 10min, still even more preferably 1.1 to 4.25 g / 10min, most preferably 1.2 to 4.0 g / 10min, for example 1.2 to 3.0 g / 10min.
[0094] The density of any LDPE polymer component (i) may be from 905 to 935 kg / m 3 , preferably 910 to 935 kg / m 3 , for example 910 to 928 kg / m 3 .
[0095] The insulating layer preferably contains no carbon black.
[0096] The insulation layer may comprise at least 90 wt% of the LDPE polymer component (i), such as at least 91 wt%, at least 92 wt%, at least 93 wt%, at least 94 wt%, in particular at least 95 wt% or at least 96 wt%, and up to 99.5 wt%, in particular up to 99 wt% of the LDPE polymer component (i), based on the total weight of the insulation layer. A blend of LDPE polymers may be used as component (i). When a blend of LDPE polymers is used, the percentage refers to the sum of the LDPE polymers contained.
[0097] The LDPE polymer component (i) generally makes up the remainder of the layer once the other components have been calculated.
[0098] Polar copolymer - a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate - insulating layer
[0099] The insulating layer further comprises a copolymer (also referred to as component (ii) or polar copolymer) comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate. Mixtures of such components (ii) may be used.
[0100] The copolymer comprising at least one polar comonomer is preferably a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate as the polymeric water tree retarder. The copolymer may be the same as or different from the low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate used for the inner and outer semiconductive layers. Generally, the definition of the low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate provided below applies to component (ii) of the insulating layer as well as component (a) of the inner and outer semiconductive layers.
[0101] The polar comonomer of the low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate is preferably selected from C1 to C6 alkyl acrylates, C1 to C6 alkyl methacrylates or vinyl acetate. Further more preferably, the LDPE copolymer used is a copolymer of ethylene and C1 to C6 alkyl acrylates, such as methyl acrylate, ethyl acrylate, propyl acrylate or butyl acrylate or vinyl acetate.
[0102] Preference is given to using ethylene methyl acrylate (EMA) copolymers, ethylene methyl methacrylate (EMMA) copolymers, ethylene ethyl acrylate (EEA) copolymers, ethylene ethyl methacrylate (EEMA) copolymers, ethylene butyl methacrylate (EBMA) copolymers, ethylene butyl acrylate (EBA) copolymers or ethylene vinyl acetate (EVA) copolymers.
[0103] Particular preference is given to using ethylene methyl acrylate (EMA), ethylene butyl acrylate (EBA) or ethylene ethyl acrylate (EEA).
[0104] The copolymer containing at least one polar comonomer in the insulating layer preferably contains 0.001 to 40 wt. %, more preferably 0.05 to 40 wt. %, further more preferably 1 to 30 wt. % of one or more comonomers, based on the total weight of the copolymer. The polar comonomer content is more preferably 5 to 30 wt. %, 5 to 25 wt. %, 5 to 20 wt. %, for example 7 to 25 wt. %, in particular 7 to 20 wt. %, 10 to 25 wt. % or 10 to 30 wt. %.
[0105] Preferably, the melt flow rate MFR2.16 / 190°C of the copolymer comprising at least one polar comonomer in the insulation layer is from 0.1 to 50 g / 10 min, more preferably from 1.0 to 30 g / 10 min, even more preferably from 2.0 to 25 g / 10 min, and most preferably from 2.0 to 22 g / 10 min. In some embodiments, the melt flow rate MFR2.16 / 190°C of the copolymer comprising at least one polar comonomer in the insulation layer is from 0.1 to 20 g / 10 min, more preferably from 0.5 to 12 g / 10 min. In a further preferred embodiment, the MFR2.16 / 190°C of the copolymer comprising at least one polar comonomer in the insulation layer is from 2.0 to 20.0 g / 10min, for example from 2.0 to 17.0 g / 10min, preferably from 2.0 to 15 g / 10min, for example from 2.0 to 13.5 g / 10min, 2.0 to 13.0 g / 10min, 2.5 to 12.5 g / 10min or from 2.5 to 12.0 g / 10min, for example from 5.0 to 12.0 g / 10min.
[0106] The density of the copolymer comprising at least one polar comonomer may be from 910 to 940 kg / m 3 , preferably 915 to 940 kg / m 3 , for example 920 to 940 kg / m 3 .
[0107] According to one embodiment, the insulation layer used in the cable core of the present invention comprises at least 0.5 wt.-% of a copolymer comprising at least one polar comonomer, i.e. component (ii), relative to the total weight of the insulation layer, preferably at least 0.60 wt.-%, for example at least 0.70 wt.-% or 0.75 wt.-%, more preferably at least 0.80 wt.-%, for example at least 0.90 wt.-%, at least 0.95 wt.-% or at least 1.0 wt.-%.
[0108] In an advantageous embodiment of the invention, the insulating layer used in the cable core of the invention comprises 9.0 wt. % or less of a copolymer comprising at least one polar comonomer, i.e. component (ii), such as 8.0 wt. % or less, preferably 7.0 wt. % or less, such as 6.0 wt. % or less, 5.0 wt. % or less, 4.0 wt. % or less or 3.0 wt. % or less, relative to the total weight of the insulating layer. When blends of these polymers are used for component (ii), the percentage refers to the sum of the copolymers comprising at least one polar comonomer contained.
[0109] In a particularly preferred embodiment of the present invention, the insulation layer used in the cable core of the present invention comprises from 0.5% to 9.0% by weight of a copolymer comprising at least one polar comonomer, i.e. component (ii), relative to the total weight of the insulation layer, preferably from 0.75% to 7.0% by weight, for example from 0.80% to 5.0% by weight, more preferably from 0.90% to 4.0% by weight, and even more preferably from 1.0% to 3% by weight.
[0110] Preferably, the amount of polar monomer units in the insulating layer is 1 micromole or more per gram, for example 2.5 micromole or more, more preferably 5 micromole or more, for example 7.5 micromole or more, further more preferably 10 micromole or more, for example 15 micromole or 20 micromole or more, based on the total amount of polymer components in the insulating layer.
[0111] Preferably, the amount of polar monomer units in the insulating layer is 150 micromoles or less, preferably 140 micromoles or less, for example 130 micromoles or less, 120 micromoles or less, more preferably 100 micromoles or less, even more preferably 80 micromoles or less, for example 75 micromoles or less, still even more preferably 70 micromoles or less, for example 60 micromoles or less, and further more preferably 50 micromoles or less, for example 40 micromoles or less, per gram, based on the total amount of polymer components in the insulating layer.
[0112] The amount of polar monomer units is expressed in micromoles per gram of all polymers (i.e. all polymer components) contained in the insulating layer. Of course, in the insulating layer, the polar monomer units are preferably substantially completely incorporated into the backbone of component (ii), i.e. the copolymer comprising at least one polar comonomer. Based on this, component (i) of the LDPE homopolymer or the LDPE copolymer with at least one polyunsaturated comonomer in the insulating layer is preferably substantially free of polar monomer units.
[0113] The present inventors have discovered that copolymers comprising at least one polar comonomer can act as polymer WTRs and thereby provide salt water wet aging performance for the insulation layer. Surprisingly, a small amount of such polar copolymers blended with component (i) in the insulation layer also provides sufficient salt water wet aging performance. Without being bound by this theory, the present inventors believe that on the one hand, it is a combination of a specific "delivery mechanism" of polar comonomers to the insulation layer (i.e., mixing the polar copolymer or component (ii) into component (i) rather than copolymerization of non-polar comonomers). The present inventors believe that in the cable core insulation layer, component (ii) forms local "islands" of polar copolymers in the LDPE phase of component (i). The above-mentioned islands of higher polarity material comprising component (ii) are believed to resist the growth of water trees, thereby improving salt water wet aging performance, while having limited impact on dielectric loss performance. On the other hand, specific selection of the total amount of polar comonomer in the insulation layer can achieve a balance between salt water wet aging performance and dielectric loss measured by tan δ, which is very suitable for submarine cables, especially submarine power cables operating at higher voltages, especially submarine AC power cables operating at higher voltages.
[0114] Crosslinker - Insulation layer
[0115] The insulating layer may be cross-linkable or cross-linked. In such cross-linkable embodiments, the cross-linkable insulating layer preferably comprises a peroxide. Once the cable core structure is formed, the cross-linkable insulating layer preferably comprises a peroxide. A mixture of peroxides may be used.
[0116] Preferred crosslinking agents are organic peroxides. Non-limiting examples are organic peroxides such as di-tert-amyl peroxide, 2,5-di(tert-butylperoxy)-2,5-dimethyl-3-hexyne, 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, tert-butylcumyl peroxide, di(tert-butyl)peroxide, dicumyl peroxide, butyl-4,4-bis(tert-butylperoxy)-valerate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxybenzoate, dibenzoyl peroxide, di(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-di(tert-butylperoxy)cyclohexane, 1,1-di(tert-amylperoxy)cyclohexane, or any mixture thereof. Preferably, the peroxide is selected from 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, di(tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, tert-butylisopropylbenzene peroxide or mixtures thereof. Most preferably, the peroxide is diisopropylbenzene peroxide.
[0117] The peroxide is preferably present in the insulation layer in an amount of less than 3.0 wt. %, preferably 0.1 to 2.5 wt. %, more preferably 0.2 to 2.5 wt. %, even more preferably 0.3 to 2.25 wt. %, for example 0.3 to 2.0 wt. %, based on the weight of the insulation layer. When a blend of crosslinking agents is used, the percentage refers to the sum of the crosslinking agents contained.
[0118] Inner semiconducting layer and outer semiconducting layer
[0119] The inner semiconducting layer and the outer semiconducting layer may be the same or different, preferably the same. Here, "same" means that the chemical composition of the inner semiconducting layer and the outer semiconducting layer is the same before crosslinking. The inner semiconducting layer and the outer semiconducting layer are different from the insulating layer.
[0120] The semiconductive property of the semiconductive layer originates from the conductive component contained in the semiconductive layer, ie, carbon black.
[0121] Preferably, both the inner and outer semiconductive layers comprise a LDPE copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate, and carbon black. Preferably, both the inner and outer semiconductive layers comprise a LDPE copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate, carbon black, a peroxide and optionally an antioxidant. The following discussion may apply to either or both semiconductive layers.
[0122] Low density polyethylene (LDPE) copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate - semiconductive layer
[0123] Said LDPE copolymer of the inner and / or outer semiconductive layer comprises a polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate or mixtures thereof. Mixtures of such LDPE copolymers may also be used.
[0124] Further preferably, the polar comonomer is selected from C1 to C6 alkyl acrylates, C1 to C6 alkyl methacrylates or vinyl acetate. Further more preferably, the LDPE copolymer used for the inner and / or outer semiconductive layers is a copolymer of ethylene and C1 to C6 alkyl acrylates (such as methyl acrylate, ethyl acrylate, propyl acrylate or butyl acrylate) or vinyl acetate.
[0125] Preference is given to using ethylene methyl acrylate (EMA) copolymers, ethylene methyl methacrylate (EMMA) copolymers, ethylene ethyl methacrylate (EEMA) copolymers, ethylene butyl methacrylate (EBMA) copolymers, ethylene ethyl acrylate (EEA) copolymers, ethylene butyl acrylate (EBA) copolymers or ethylene vinyl acetate (EVA) copolymers.
[0126] Particular preference is given to using ethylene methyl acrylate (EMA), ethylene butyl acrylate (EBA) or ethylene ethyl acrylate (EEA).
[0127] The LDPE copolymer of the inner and / or outer semiconductive layer preferably comprises 0.001 to 40 wt.-%, more preferably 0.05 to 40 wt.-%, even more preferably 1 to 30 wt.-%, of one or more comonomers, based on the total weight of the LDPE copolymer. The polar comonomer content is more preferably 5 to 30 wt.-%, 5 to 25 wt.-%, 5 to 20 wt.-%, e.g. 7 to 20 wt.-% or 10 to 20 wt.-%.
[0128] Preferably, the LDPE copolymer of the inner and / or outer semiconductive layer has a melt flow rate MFR2.16 / 190°C of 0.1 to 50 g / 10 min, more preferably 1.0 to 30 g / 10 min, even more preferably 2.0 to 25 g / 10 min, yet even more preferably 3.0 to 22.0 g / 10 min, and most preferably 4.0 to 21.0 g / 10 min, for example 5.0 to 20.0 g / 10 min.
[0129] The density of LDPE copolymer can be 910 to 940 kg / m 3 , preferably 915 to 940 kg / m 3 , for example 920 to 940 kg / m 3 .
[0130] The inner and / or outer semiconductive layer may comprise at least 50 wt%, such as at least 55 wt%, of LDPE copolymer, based on the total weight of the respective semiconductive layer. When a blend of LDPE copolymers is used, the percentage refers to the sum of the LDPE copolymers contained.
[0131] In some embodiments, at least 60 wt% of the LDPE copolymer is present in the inner and / or outer semiconductive layer, based on the total weight of the respective semiconductive layer. Once the other components of the semiconductive layer are selected, the LDPE copolymer typically constitutes the remainder of the layer. The inner and / or outer semiconductive layer preferably contains no more than 90 wt% of the LDPE copolymer.
[0132] Aggregation methods
[0133] Typically, any LDPE homopolymer or copolymer of the present invention, as described above or in any of the following sections, can be produced by any conventional polymerization process. Preferably, it is produced by free radical polymerization, such as high-pressure free radical polymerization. High-pressure polymerization can be carried out in a tubular reactor or an autoclave reactor. Preferably, it is a tubular reactor. Typically, the pressure can be in the range of 1200 to 3500 bar and the temperature can be in the range of 150° C. to 350° C. For more detailed information on high-pressure free radical polymerization, see Encyclopedia of Polymer Science and Engineering, Vol. 6 (1986), pp. 383-410 and Encyclopedia of Materials: Science and Technology, Elsevier Science & Technology Ltd.: Polyethylene: High-pressure, R. Klimesch, D. Littmann and F.O. Pages 7181-7184 (2001), which is incorporated herein by reference.
[0134] As is well known, propylene, for example, can be used as a comonomer or chain transfer agent (CTA), or both, whereby it can contribute to the total amount of carbon-carbon double bonds, preferably to the total amount of vinyl groups. For the purposes of the present invention, if a compound that can also act as a comonomer is specifically used as a CTA during the polymerization to provide double bonds, the copolymerizable comonomer is not counted in the comonomer content. For the purposes of the present invention, propylene can be used as a CTA and can contribute to the total amount of vinyl groups, but it is not counted in the comonomer content.
[0135] Carbon black - semi-conductive layer
[0136] According to the invention, the inner semiconducting layer and the outer semiconducting layer further comprise carbon black.
[0137] The semiconductive properties are derived from the added carbon black. Therefore, the amount of carbon black is at least sufficient to obtain a semiconductive layer. Preferably, the inner and / or outer semiconductive layer comprises 10 to 60 wt.-%, preferably 15 to 48 wt.-%, of carbon black, based on the total weight of the respective semiconductive layer. In other preferred embodiments, the amount of carbon black is 10 to 45 wt.-%, for example 20 to 45 wt.-%, preferably 25 to 45 wt.-%, more preferably 25 to 40 wt.-%, or in particular 30 to 41 wt.-%, based on the weight of the respective semiconductive layer.
[0138] Any conductive carbon black may be used. Examples of suitable carbon blacks include furnace black and acetylene black. Mixtures may also be used. When a blend of carbon blacks is used, the percentage refers to the sum of the carbon blacks contained.
[0139] The carbon black may have a nitrogen surface area (BET) of 5 to 400 m2 when measured according to ASTM D3037-93. 2 / g, for example 10 to 300 m 2 / g, for example 30 to 200 m 2 / g. In addition, carbon black may have one or more of the following properties:
[0140] i) a primary particle size of at least 5 nm, which is defined as the number average particle size according to ASTM D3849-95a;
[0141] ii) an iodine adsorption number (IAN) of at least 10 mg / g, such as 10 to 300 mg / g, such as 30 to 200 mg / g, as determined according to ASTM D1510; and / or
[0142] iii) a DBP (dibutyl phthalate) adsorption value (= oil adsorption value) of at least 30 cm-1, measured according to ASTM D2414 3 / 100g, e.g. 60 to 300cm 3 / 100g, e.g. 70 to 250cm 3 / 100g, e.g. 80 to 200cm 3 / 100g, e.g. 90 to 180cm 3 / 100g.
[0143] Additionally, carbon black may have one or more of the following properties:
[0144] a) a primary particle size of at least 5 nm, which is defined as the number average particle size according to ASTM D3849-95a;
[0145] b) an iodine adsorption value of at least 30 mg / g according to ASTM D1510;
[0146] c) an oil adsorption value of at least 30 mL / 100 g as measured according to ASTM D2414.
[0147] The average primary particle size of a group of furnace blacks suitable for use is 28 nm or less. The average primary particle size is defined as the number average particle size measured according to ASTM D3849-95a. According to ASTM D1510, the iodine adsorption value of such particularly suitable furnace blacks may be 60 to 300 mg / g. Further suitable is (such) oil adsorption value of 50 to 225 mL / 100 g, for example 50 to 200 mL / 100 g, and this value is measured according to ASTM D2414.
[0148] Another group of furnace blacks that are also suitable has an average primary particle size greater than 28 nm. The average primary particle size is defined as the number average particle size measured according to ASTM D3849-95a. According to ASTM D1510, the iodine adsorption value of such furnace blacks that are suitable is 30 to 200 mg / g. In addition, according to ASTM D2414, the oil adsorption value is, for example, 80 to 300 mL / 100 g.
[0149] Other suitable carbon blacks may be prepared by any other process or may be further processed.
[0150] The carbon black suitable for the semiconductive layer of the cable core is characterized by its cleanliness. Thus, suitable carbon black has an ash content of less than 0.2% by weight as measured according to ASTM D1506, a 325 mesh residue of less than 30 ppm as measured according to ASTM D1514, and a total sulfur content of less than 1% by weight as measured according to ASTM D1619.
[0151] Furnace black is a well-known term referring to a well-known type of carbon black produced in a furnace reactor. For examples of carbon black, its preparation method and reactor, reference may be made, for example, to EP-A-0629222, US 4,391,789, US 3,922,335 and US 3,401,020 to Cabot. As examples of commercial furnace black grades, N115, N220 and N550 described in ASTM D 1765-98b may be mentioned. Furnace black is usually distinguished from acetylene black, which is another type of carbon black suitable for use in semiconductive layers. Acetylene black is produced in the acetylene black process by the reaction of acetylene with an unsaturated hydrocarbon, as described in US 4,340,577.
[0152] The acetylene black of the present invention is generally used for preparing acetylene black.According to the invention, the acetylene black of the present invention can be used for preparing acetylene black.Especially, the average primary particle size of acetylene black can be greater than 20nm, for example 20 to 80nm.Average primary particle size is defined as the number average particle size measured according to ASTM D3849-95a.According to ASTM D1510, the iodine adsorption value of this type of acetylene black that is suitable for is 30 to 300mg / g, for example 30 to 150mg / g.In addition, (this type of) oil adsorption value is for example 80 to 300mL / 100g, for example 100 to 280mL / 100g, and this value is measured according to ASTM D2414.Acetylene black is a generally recognized term and is well-known, and the acetylene black for example provided by Denka.
[0153] According to another embodiment of the present invention, a semiconductive layer is disclosed, wherein the conductive component comprises or consists of conductive carbon black, such as carbon black having one or more (e.g., all) of the following properties:
[0154] The primary particle size is at least 5 nm, which is defined as the number average particle size according to ASTM D3849-95a;
[0155] An iodine adsorption number (IAN) of at least 10 mg / g, e.g., 10 to 300 mg / g, as determined according to ASTM D1510; or
[0156] DBP (dibutyl phthalate) adsorption value (= oil adsorption value) of at least 30 cm according to ASTM D2414 3 / 100g, e.g. 60 to 300cm 3 / 100g.
[0157] Crosslinker - Semiconducting layer
[0158] The inner and / or outer semiconductive layer is crosslinkable or crosslinked. Various crosslinking methods can be envisaged, however, to this extent, the crosslinking agent, preferably a peroxide, is preferably present in the crosslinkable inner and / or outer semiconductive layer in an amount of less than 3.0 wt.-%, more preferably 0.1 to 2.5 wt.-%, even more preferably 0.3 to 2.5 wt.-%, based on the total weight of the respective semiconductive layer. In some embodiments, the peroxide is present in an amount of 0.4 to 2.5 wt.-%, preferably 0.4 to 2.0 wt.-%, for example 0.4 to 1.4 wt.-%, based on the total weight of the respective semiconductive layer. When a blend of crosslinking agents is used, the percentage refers to the sum of the crosslinking agents contained.
[0159] Preferred crosslinking agents are organic peroxides. Non-limiting examples are organic peroxides such as di-tert-amyl peroxide, 2,5-di(tert-butylperoxy)-2,5-dimethyl-3-hexyne, 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, tert-butylcumyl peroxide, di(tert-butyl)peroxide, dicumyl peroxide, butyl-4,4-bis(tert-butylperoxy)-valerate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxybenzoate, dibenzoyl peroxide, di(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-di(tert-butylperoxy)cyclohexane, 1,1-di(tert-amylperoxy)cyclohexane, or any mixture thereof. Preferably, the peroxide is selected from 2,5-di(tert-butylperoxy)-2,5-dimethylhexane, di(tert-butylperoxyisopropyl)benzene, diisopropylbenzene peroxide, tert-butylisopropylbenzene peroxide or mixtures thereof. Most preferably, the peroxide is di(tert-butylperoxyisopropyl)benzene.
[0160] Antioxidants
[0161] Any layer of the submarine cable core may contain an antioxidant. As antioxidants, mention may be made of hindered or semi-hindered phenols, aromatic amines, aliphatic hindered amines, organic phosphates, thio compounds, polymeric 2,2,4-trimethyl-1,2-dihydroquinoline and mixtures thereof.
[0162] More preferably, the antioxidant is selected from the group consisting of 4,4'-bis(1,1'-dimethylbenzyl)diphenylamine, p-styrenated diphenylamine, 4,4'-thiobis(2-tert-butyl-5-methylphenol), polymeric 2,2,4-trimethyl-1,2-dihydroquinoline or derivatives thereof.
[0163] More preferably, the antioxidant is selected from (but not limited to) the group consisting of 4,4'-bis(1,1'-dimethylbenzyl)diphenylamine, para-styrenated diphenylamine, 4,4'-thiobis(2-tert-butyl-5-methylphenol), 2,2'-thiobis(6-tert-butyl-4-methylphenol), distearyl thiodipropionate, 2,2'-thiodiethylbis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, polymerized 2,2,4-trimethyl-1,2-dihydroquinoline or its derivatives. Of course, not only one of the above antioxidants can be used, but also any mixture thereof.
[0164] The amount of the antioxidant, optionally a mixture of two or more antioxidants, based on the total weight of the respective semiconductive layer, may be 0.005 to 2.5 wt.-%, for example 0.01 to 2.5 wt.-%, preferably 0.01 to 2.0 wt.-%, more preferably 0.03 to 2.0 wt.-%, in particular 0.03 to 1.5 wt.-%, more particularly 0.05 to 1.5 wt.-%, for example 0.05 to 1.3 wt.-%, or 0.1 to 1.5 wt.-%, for example 0.1 to 1.25 wt.-%.
[0165] In some embodiments, the amount of antioxidant, optionally a mixture of two or more antioxidants, is 0.03 to 2.0 wt %, preferably 0.04 to 1.5 wt %, for example 0.05 to 1.0 wt %, more preferably 0.05 to 0.8 wt %, for example 0.05 to 0.7 wt % or 0.05 to 0.35 wt %, especially 0.07 to 0.6 wt %, more especially 0.08 to 0.5 wt %, for example 0.09 to 0.4 wt % or 0.1 to 0.35 wt %, based on the total weight of the insulating layer.
[0166] Other components
[0167] The inner semiconducting layer and / or the outer semiconducting layer or the insulating layer may comprise further additives. As possible additives there may be mentioned scorch retardants, crosslinking accelerators, stabilizers, processing aids, flame retardant additives, acid scavengers, inorganic fillers, voltage stabilizers or mixtures thereof.
[0168] "Anti-scorch agents" are defined as compounds which reduce premature crosslinking, i.e. the formation of scorch during the extrusion process. In addition to the anti-scorch properties, anti-scorch agents may also simultaneously produce further effects, such as a promoting effect, i.e. an enhanced crosslinking performance. The use of anti-scorch agents in the insulating layer is particularly preferred.
[0169] Useful scorch retarders can be selected from unsaturated dimers of aromatic α-methyl olefin monomers, substituted or unsubstituted diphenylethylene, quinone derivatives, hydroquinone derivatives such as 2,5-di-tert-butylhydroquinone, esters and ethers containing monofunctional vinyl groups, or mixtures thereof. More preferably, the scorch retarders are selected from unsaturated dimers of aromatic α-methyl olefin monomers such as 2,4-diphenyl-4-methyl-1-pentene, substituted or unsubstituted diphenylethylene, or mixtures thereof. A highly preferred choice is 2,4-diphenyl-4-methyl-1-pentene.
[0170] Preferably, the amount of scorch retarder is in the range of 0.005 to 1.0 wt.-%, more preferably in the range of 0.01 to 0.80 wt.-%, based on the weight of the layer. Further preferred ranges are 0.03 to 0.75 wt.-%, 0.05 to 0.50 wt.-%, 0.05 to 0.70 wt.-% and 0.10 to 0.50 wt.-%, based on the total weight of the layer.
[0171] The crosslinking promoter may be a compound containing at least two unsaturated groups, such as an aliphatic or aromatic compound, an ester, an ether, an amine or a ketone, which contains at least two unsaturated groups, such as a cyanurate, an isocyanurate, a phosphate, an orthoformate, an aliphatic or aromatic ether, or an allyl ester of benzenetricarboxylic acid. Examples of esters, ethers, amines and ketones are compounds selected from the general group of diacrylates, triacrylates, tetraacrylates, triallyl cyanurate, triallyl isocyanurate, 3,9-divinyl-2,4,8,10-tetra-oxaspiro[5,5]-undecane (DVS), triallyl trimellitate (TATM) or N,N,N',N',N",N"-hexaallyl-1,3,5-triazine-2,4,6-triamine (HATATA) or any mixture thereof. Based on the total weight of the layer, the added amount of the crosslinking promoter can be less than 2.0 wt%, such as less than 1.5 wt%, such as less than 1.0 wt%, such as less than 0.75 wt%, such as less than 0.5 wt%, and its lower limit is, for example, at least 0.05 wt%, such as at least 0.1 wt%.
[0172] In another embodiment of the present invention, the insulating layer does not contain any water tree retarder other than component (ii) discussed herein.
[0173] Preparation of polymer compositions
[0174] In the process of preparing the polymer composition, the components may be blended, for example melt mixed in a compounding device. Preferably, the method does not involve the use of peroxides. Typically, the method involves heating to a temperature of at least 150°C, preferably at least 160°C, for example at least 170°C. The method typically involves heating to 300°C or less, for example 250°C or less.
[0175] It should be understood that all definitions and preferences as described above apply equally to all other embodiments described below. In one embodiment, the insulation layer composition of the present invention may include a crosslinking agent before the composition is used in cable production, whereby the polymer components and the crosslinking agent may be blended by any conventional mixing method, such as by adding the crosslinking agent to the melt of the polymer composition, such as in an extruder, or by adsorbing a liquid peroxide, a liquid peroxide or a peroxide dissolved in a solvent onto a solid polymer composition (e.g., particles thereof). The resulting component insulation layer composition, its components such as polymer components (i) and (ii), an antioxidant and a crosslinking agent are then used in the preparation of an article, such as a cable core preparation process.
[0176] In another embodiment, the crosslinking agent can be added in a step of preparing the crosslinkable article and also forms the insulation layer composition used in the cable core of the present invention. When the crosslinking agent is added during the preparation of the article, the crosslinking agent, for example, as described herein, is added in liquid form at ambient temperature, or preheated to above its melting point, or dissolved in a carrier medium, which is well known in the art.
[0177] The insulation layer composition used for the cable core of the present invention may also include additional additives, or additional additives may be blended into the polymer composition during the preparation of the article comprising the insulation layer composition. It should be understood that additional additives may be added in the form of a masterbatch, including any antioxidant, crosslinking agent, scorch retardant, which is well known in the art.
[0178] In a particular embodiment, the semiconductive layer used in the cable core of the present invention can be obtained in a variety of ways using a variety of different production technologies, such as closed mixers such as Banbury or Bolling, continuous single screw mixers such as BUSS, or continuous twin screw mixers such as Farrel or Werner & Pfleiderer. The type of mixer and the selected operating conditions for preparing the semiconductive compound will have a direct impact on the melt quality and will affect the final compound properties, such as melt flow rate, volume resistivity and surface smoothness. Particularly useful is the co-kneader technology (BUSS, X-compound). In the preparation of the semiconductive layer, conductive fillers can be added to the polymer in the molten state under full control of the production temperature. Utilizing this technology, those skilled in the art can achieve blends with fully improved dispersion and distribution mixing.
[0179] It will be appreciated that the crosslinking agent is generally added to the semiconductive layer composition in a similar manner to the insulating layer composition, which is described in detail in the above embodiments.
[0180] conductor
[0181] The submarine cable core of the present invention comprises a conductor. The conductor can be made of any suitable conductive metal, such as copper or aluminum.
[0182] Submarine cables and cable cores
[0183] A submarine power cable is defined as a cable comprising at least one cable core, operating at any voltage, preferably operating at a voltage above 30 kV to transmit energy. It should be understood that all definitions and preferences as described above apply equally to all other embodiments as described below.
[0184] The voltage applied to the submarine power cable may be an alternating current (AC), a direct current (DC) or a transient (pulse) voltage. In addition, the submarine cable according to the present invention is very advantageously a submarine AC power cable, such as a submarine cable operating at a voltage of 1 to 525 kV, 6 to 525 kV, 36 to 275 kV, such as 66 to 275 kV, 36 to 220 kV, such as 66 to 220 kV, 36 to 150 kV, such as 66 to 150 kV and above 66 kV (RMS voltage, the voltage between any two conductors in a three-phase cable). In some embodiments, the submarine cable is a submarine AC power cable operating at a voltage equal to or higher than 33 kV, preferably equal to or higher than 36 kV, preferably equal to or higher than 66 kV. In some embodiments, the submarine cable is an AC power cable operating at a voltage below 550 kV, preferably below 525 kV, preferably below 400 kV, more preferably below 380 kV, especially below 275 kV, below 220 kV or below 150 kV.
[0185] As is known, a submarine cable may optionally comprise further layers, such as a layer surrounding the outer semiconductive layer, such as a sheath layer.The presence of a moisture barrier to prevent the ingress of water is preferably avoided, ie the submarine cable is a wet design cable.
[0186] A submarine cable core for a submarine cable can be produced by a method comprising step (a)
[0187] - providing and mixing, e.g. melt mixing in an extruder, a crosslinkable first semiconductive layer composition for the inner semiconductive layer,
[0188] - providing and mixing, e.g. melt mixing in an extruder, a crosslinkable insulation layer composition for the insulation layer,
[0189] - providing and mixing, e.g. melt mixing in an extruder, a second semiconductive layer composition for the outer semiconductive layer,
[0190] (b) applied to a conductor, for example by coextrusion,
[0191] - a melt mixture of the first semiconducting layer composition obtained in step (a) to form an inner semiconducting layer,
[0192] - a melt mixture of the insulating layer composition obtained in step (a) to form an insulating layer, and
[0193] - a melt mixture of the second semiconducting layer composition obtained from step (a) to form the outer semiconducting layer, and
[0194] (c) crosslinking one or more of the insulation layer, the inner semiconductive layer and the outer semiconductive layer of the obtained submarine cable core, optionally under crosslinking conditions.
[0195] It should be understood that the compositions of the layers of the present invention may contain a crosslinking agent before the composition is used in the production of the cable, or the crosslinking agent may be added in a step in the preparation of the crosslinkable article.
[0196] Preferably, if peroxide is used in the manufacture of a layer of the submarine cable core, the layer is crosslinked. Hence, the submarine cable core is crosslinkable.
[0197] The first semiconductive composition for the inner semiconductive layer, the crosslinkable insulating composition for the insulating layer and the second semiconductive composition for the outer semiconductive layer comprise the components necessary to form the inner, insulating and outer semiconductive layers, respectively, of a submarine cable core.
[0198] Preferably, all layers are crosslinked.The present invention therefore also provides a crosslinked submarine cable core obtained by crosslinking a submarine cable core as defined herein.
[0199] The cross-linking process may be carried out at elevated temperatures, for example above 150°C, such as from 160 to 350°C.
[0200] Melt mixing refers to mixing at a temperature above the melting point of at least the major polymer component of the resulting mixture, typically at least 10 to 15°C above the melting or softening point of the polymer components.
[0201] The term "coextrusion" herein refers to the use of one or more extrusion heads to form all or part of a layer simultaneously. For example, triple extrusion can be used to form three layers.
[0202] In a further embodiment of the present invention, as described in the determination method section below, the crosslinked submarine cable core of the present invention has a tan δ of at most 4.5·10 -4 , preferably at most 4·10 -4 , for example 3.5·10 -4 , even more preferably at most 3·10 -4 , for example 2.5·10 -4 , and / or tan δ measured on a 10 kV cable at 90 °C and 10 kV / mm is at most 12 · 10 -4 , preferably at most 10·10 -4 , for example 8.10 -4 , even more preferably at most 7.5·10 -4 , for example 6.5·10 -4 .
[0203] In a further embodiment of the present invention, as described in the determination method section below, the crosslinked submarine cable of the present invention has an AC breakdown strength value (or Weibull Eb) measured on a 20 kV cable (5.5 mm nominal insulation thickness) after wet aging in salt water for 1 year of at least 40 kV / mm, such as at least 41 kV / mm, 42 kV / mm, 43 kV / mm or 44 kV / mm, preferably at least 45 kV / mm, more preferably at least 46 kV / mm, even more preferably at least 47 kV / mm, and most preferably at least 48 kV / mm. It should be understood that the upper limit of the AC breakdown strength value (or Weibull Eb) measured on a 20 kV cable (5.5 mm nominal insulation thickness) after wet aging in salt water for 1 year, as described in the determination method section below, is not particularly limited, but is preferably less than 60 kV / mm or less than 55 kV / mm.
[0204] Furthermore, the first semiconducting composition and the second semiconducting composition may, for example, be identical.
[0205] The thickness of the insulation layer of a submarine power cable, such as a submarine AC cable, is typically 2 mm or more, such as at least 2.5 mm, at least 3 mm, such as at least 3.5 to 50 mm, such as 4 to 50 mm, preferably at least 4.5 to 35 mm, such as 5 to 30 mm, when measured from a cross section of the insulation layer of the submarine cable.
[0206] The thickness of the inner and / or outer semiconductive layer of the submarine power cable may typically be in the range of 0.4 mm or more, such as 0.5 mm or more, such as 0.7 mm to 5.0 mm, when measured in a cross section of the layer.
[0207] Viewed from another aspect, the present invention provides a submarine cable, preferably a submarine power cable, more preferably a submarine AC power cable, comprising at least one cable core, the cable core comprising a conductor, the conductor being surrounded in sequence at least by an inner semiconducting layer, an insulating layer and an outer semiconducting layer;
[0208] Wherein, based on the total weight of each semiconductive layer, the inner semiconductive layer and / or the outer semiconductive layer independently comprises:
[0209] at least 50 wt.% of a LDPE copolymer having a polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate;
[0210] 25 to 48 wt % carbon black; and
[0211] 0.1 to 2.5 wt. % peroxide; and
[0212] Wherein, based on the total weight of the insulating layer, the insulating layer comprises:
[0213] (i) a low density polyethylene homopolymer or a low density polyethylene copolymer having at least one polyunsaturated comonomer and optionally one or more other comonomers; and
[0214] (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate;
[0215] (iii) 0.1 to 2.5% by weight of a peroxide;
[0216] Wherein, the amount of the polar monomer unit in the insulating layer is 1 to 150 micromoles per gram based on the total amount of the polymer component in the insulating layer.
[0217] use
[0218] The submarine cable of the present invention is a submarine cable particularly suitable for use in saltwater environments, especially high pressure environments. Therefore, the cable can be buried on the seabed, or it can also be located in the sea or on the seabed. Submarine cables buried on land but close to the coast may also encounter saltwater environments underground. Submarine cables used in tidal estuaries may also be affected by saltwater. The cable of the present invention can also be used in saltwater lakes and saltwater seas, for example in such water bodies or under such water bodies. The cable of the present invention is suitable for use in any saltwater environment. It should also be understood that all definitions and preferences as described above are equally applicable to all other embodiments described below.
[0219] Thus, viewed from another aspect, the invention provides a submarine cable comprising at least one, preferably at least two, more preferably at least three submarine cable cores as hereinbefore defined.
[0220] In a preferred embodiment according to the present invention, the submarine cable is a submarine AC cable comprising at least three submarine cable cores as defined above.
[0221] In a more preferred embodiment of the invention, the submarine cable is a submarine high voltage (HV) AC cable comprising at least three submarine cable cores as defined hereinbefore and operating at a voltage of at least 30 kV.
[0222] In one embodiment, the invention relates to a method comprising burying a submarine cable as defined above in the seabed.
[0223] In one embodiment, the invention relates to a method comprising laying a submarine cable as defined above on the seabed. The submarine cable may thus be dispensed from a spool. The method may involve a submarine cable laying vessel.
[0224] In one embodiment, the submarine cable of the present invention may be used to connect an offshore power generation system to the coast, whereby the submarine cable is located on the seabed.
[0225] Therefore, from another aspect, the present invention provides a power generation system, comprising:
[0226] (A) offshore generators, such as wind turbines;
[0227] (B) A submarine cable as claimed herein, connecting said offshore generator via the sea or seabed to a substation located offshore and / or onshore.
[0228] Offshore wind turbines are typically located on offshore platforms and are connected to offshore substations and / or onshore substations located on separate platforms via submarine cables. The submarine cables and submarine cable cores of the present invention perform well in the presence of seawater and are well suited for this purpose.
[0229] Therefore, in general, the submarine cable of the present invention can connect offshore equipment to onshore equipment or other offshore equipment. Therefore, the submarine cable of the present invention can connect these equipment via the sea or the seabed.
[0230] In one embodiment, the submarine cable of the present invention can be used to distribute electricity generated by an offshore power generation system and connect the offshore power generation system to a substation or collection system located offshore and / or onshore via the sea or seabed.
[0231] In one embodiment, the present invention relates to a method for operating a submarine cable, comprising:
[0232] Provided is a submarine cable, comprising:
[0233] - three submarine cable cores, as defined above;
[0234] - Armouring around three submarine cable cores;
[0235] Alternating current is transmitted through the three submarine cable cores.
[0236] According to one embodiment, transmitting the alternating current comprises supplying the alternating current generated by the wind farm system to a corresponding onshore substation. According to another embodiment, transmitting the alternating current comprises supplying the alternating current from the onshore substation to the wind farm system.
[0237] The submarine cable of the invention is particularly suitable for use in power plants, such as offshore wind farms, tidal or wave systems.
[0238] The invention will now be described with reference to the following non-limiting examples.
[0239] Determination method
[0240] Unless otherwise stated in the description or experimental section, the following methods were used for characterization.
[0241] wt%: weight percentage
[0242] Melt flow rate
[0243] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indicator of the flowability of the polymer and therefore also of its processability. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR of polyethylene is determined at 190°C and can be determined at different loads, for example 2.16 kg (MFR2) or 21.6 kg (MFR 21 ).
[0244] density
[0245] Density was measured according to ISO 1183-1 / Method A. Sample preparation was done by compression molding according to ISO 17855-2:2016.
[0246] Comonomer content
[0247] a) Quantitative analysis of α-olefin content in low density polyethylene by nuclear magnetic resonance (NMR) spectroscopy:
[0248] The comonomer content was determined by quantitative 13C nuclear magnetic resonance (NMR) spectroscopy after elementary partitioning (J. Randall JMS-Rev. Macromol. Chem. Phys., C29 (2&3), 201-317 (1989)). The experimental parameters were adjusted to ensure the measurement of quantitative spectra for this specific task.
[0249] Specifically, solution-state NMR spectroscopy was performed using a Bruker AvanceIII 400 spectrometer. A homogenous sample was prepared by dissolving about 0.200 g of polymer in 2.5 mL of deuterated tetrachloroethylene in a 10 mm sample tube at 140° C. using a heating block and a rotating tube furnace. Proton decoupled 13C single pulse NMR spectra with NOE (power gating) were recorded using the following acquisition parameters: 90° rotation angle, 4 virtual scans, 4096 transients, 1.6 sec acquisition time, spectral width 20 kHz, temperature 125° C., dual-level WALTZ proton decoupling scheme, and 3.0 sec relaxation delay. The resulting FID was processed using the following processing parameters: zero filling of 32 k data points and apodisation using a Gaussian window function; automatic zero- and first-order phase correction and automatic baseline correction using a fifth-order polynomial restricted to the region of interest.
[0250] Quantities were calculated using simple corrected ratios of signal integrals from representative sites based on methods well known in the art.
[0251] b) Determination of polar comonomer content in low density polyethylene
[0252] The comonomer content (% by weight) is determined in a known manner based on Fourier transform infrared spectroscopy (FTIR) calibrated with quantitative nuclear magnetic resonance (NMR) spectroscopy.
[0253] The film was pressed using a Specac film press at 150°C with a pressure of about 5 tons for 1 to 2 minutes and then cooled with cold water in an uncontrolled manner. The exact thickness of the resulting film sample was measured.
[0254] After FTIR analysis, a baseline of the absorbance pattern is drawn for the peak to be analyzed. The absorbance peak of the comonomer is normalized to the absorbance peak of polyethylene. The FTIR peak height ratio is related to the polar comonomer content of the reference material determined by NMR. The NMR spectroscopy calibration procedure is performed in a conventional manner well documented in the literature.
[0255] Quantification of polar comonomer content in polymers by NMR spectroscopy
[0256] The polar comonomer content is determined by quantitative nuclear magnetic resonance (NMR) spectroscopy after basic partitioning (e.g., "NMR Spectra of Polymers and Polymer Additives", AJ Brandolini and DD Hills, 2000, Marcel Dekker, Inc., New York). The experimental parameters are adjusted to ensure that quantitative spectra are measured for this specific task (e.g., "200 and More NMR Experiments: A Practical Course", S. Berger and S. Braun, 2004, Wiley-VCH, Weinheim). The quantity is calculated in a manner known in the art using simple corrected ratios of the signal integrals of representative sites.
[0257] The following is an example of the determination of the polar comonomer content of ethylene ethyl acrylate, ethylene butyl acrylate and ethylene methyl acrylate.
[0258] The weight percentage can be converted into mole percentage by calculation. This is well documented in the literature.
[0259] (1) Ethylene copolymer containing butyl acrylate
[0260] Polymer film samples were prepared for FTIR measurements: 0.5 to 0.7 mm thickness for butyl acrylate with an ethylene butyl acrylate content greater than 6 wt %, and 0.05 to 0.12 mm thickness for butyl acrylate with an ethylene butyl acrylate content less than 6 wt %.
[0261] After FT-IR analysis, 3450cm -1 The maximum absorbance peak at 3510 cm-1 minus the maximum absorbance peak at butyl acrylate content greater than 6 wt% -1 The absorbance value at the baseline (A 丙烯酸丁酯 –A 3510 ). Then 2020cm -1 The maximum absorbance of the polyethylene peak at 2120 cm minus the peak at 2120 cm -1 The absorbance value at the baseline (A 2020 –A 2120). Then the calculation (A) is done in the conventional manner well documented in the literature. 丙烯酸丁酯 –A 3510 ) and (A 2020 –A 2120 ) between them.
[0262] 1165cm -1 The maximum absorbance peak at 1865 cm-1 minus the maximum absorbance peak at butyl acrylate comonomer content less than 6 wt% -1 The absorbance value at the baseline (A 丙烯酸丁酯 –A 1865 ). Then 2660cm -1 The maximum absorbance of the polyethylene peak at 1865 cm minus the peak at 1865 cm -1 The absorbance value at the baseline (A 2660 –A 1865 ). Then calculate (A 丙烯酸丁酯 –A 1865 ) and (A 2660 –A 1865 ) between them.
[0263] (2) Ethylene copolymer containing ethyl acrylate
[0264] Polymer film samples were prepared for FTIR measurements: 0.5 mm thickness for ethylene ethyl acrylate.
[0265] After FT-IR analysis, the 3450 cm -1 The maximum absorbance of the ethyl acrylate peak (A 丙烯酸乙酯 ), and at about 3205 and 3295cm -1 A linear baseline correction was performed. Then the 2020 cm -1 The maximum absorbance of the polyethylene peak (A 2020 ), and at about 1975 and 2120cm -1 A linear baseline correction was performed. Then, the (A 丙烯酸乙酯 ) and (A 2020 ) between them.
[0266] (3) Ethylene copolymer containing methyl acrylate
[0267] Polymer film samples were prepared for FTIR measurements: 0.1 mm thickness for methyl acrylate with an ethylene methyl acrylate content greater than 8 wt %, and 0.05 mm thickness for methyl acrylate with an ethylene methyl acrylate content less than 8 wt %.
[0268] After analysis, 3455cm -1 The maximum absorbance peak at 3510 cm-1 minus the maximum absorbance peak at methyl acrylate content greater than 8 wt%-1 The absorbance value at the baseline (A 丙烯酸甲酯 –A 3510 ). Then 2675cm -1 The maximum absorbance of the polyethylene peak at 2450 cm minus the peak at 2450 cm -1 The absorbance value at the baseline (A 2675 –A 2450 ). Then the calculation (A) is done in the conventional manner well documented in the literature. 丙烯酸甲酯 –A 3510 ) and (A 2675 –A 2450 ) between them.
[0269] 1164cm -1 The maximum absorbance peak at which the methyl acrylate comonomer content is less than 8 wt% minus 1850 cm -1 The absorbance value at the baseline (A 丙烯酸甲酯 –A 1850 ). Then 2665cm -1 The maximum absorbance of the polyethylene peak at 1850 cm minus the peak at 1850 cm -1 The absorbance value at the baseline (A 2665 –A 1850 ). Then calculate (A 丙烯酸甲酯 –A 1850 ) and (A 2665 –A 1850 ) between them.
[0270] ASTM D3124-98 and ASTM D6248-98 methods are used to determine the amount of double bonds in polymers (i.e. polyethylene)
[0271] ASTM D3124-98 and ASTM D6248-98 methods are suitable for determining double bonds in LDPE component (i). In this method description, LDPE component (i) is referred to as "polymer".
[0272] On the one hand, ASTM D3124-98 and ASTM D6248-98 methods include procedures for determining the amount of double bonds / 1000 carbon atoms based on the ASTM D3124-98 method. In the ASTM D3124-98 method, the determination of vinylidene / 1000 carbon atoms is described in detail based on 2,3-dimethyl-1,3-butadiene. In the ASTM D6248-98 method, the determination of vinyl and trans-vinylidene / 1000 carbon atoms is described in detail based on 1-octene and trans-3-hexene, respectively. The sample preparation procedures described therein have been applied to the determination of vinyl / 1000 carbon atoms, vinylidene / 1000 carbon atoms and trans-vinylidene / 1000 carbon atoms in the present invention. The ASTM D6248-98 method proposes that the bromination procedure in the ASTM D3124-98 method may be included, but the samples of the present invention are not treated with bromination. To determine the extinction coefficients of the three double bonds, the following three compounds were used: 1-decene for vinyl, 2-methyl-1-heptene for vinylidene, and trans-4-decene for trans-vinylene, and the procedures described in ASTM D3124-98 and ASTM D6248-98 were followed except for the above exceptions.
[0273] The total amount of vinyl bonds, vinylidene bonds and trans-vinylidene double bonds of the "polymer" was analyzed by IR spectroscopy and expressed as the amount of vinyl bonds, vinylidene bonds and trans-vinylidene bonds per 1000 carbon atoms.
[0274] The polymer to be analyzed was pressed into a film with a thickness of 0.5 to 1.0 mm. The actual thickness was measured. FT-IR analysis was performed on a PerkinElmer Spectrum One. -1 Two scans were recorded at a resolution of .
[0275] 1) A polymer composition comprising polyethylene homopolymers and copolymers, or a Polymer compositions, other than polyethylene copolymers containing more than 0.4% by weight of polar comonomer
[0276] Three types of C=C containing functional groups in polyethylene were quantified, each with a characteristic absorption and calibrated to different model compounds to derive their own extinction coefficients:
[0277] Based on 1-decene [dec-1-ene], by 910 cm -1 The vinyl group (R-CH=CH2) gives E=13.13 L·mol -1 mm -1
[0278] Based on 2-methyl-1-heptene [2-methylhept-1-ene], by 888cm -1The vinylene (RR'C=CH2) gives E=18.24L·mol -1 mm -1
[0279] Based on trans-4-decene [(E)-dec-4-ene], by 965cm -1 The trans-vinylene (R-CH=CH-R') gave E=15.14 L·mol -1 mm -1
[0280] For polyethylene homopolymers or copolymers containing less than 0.4 wt.% polar comonomer, the polar comonomer content is about 980 and 840 cm -1 A linear baseline correction was performed.
[0281] 2) A polymer composition comprising a polyethylene copolymer, or comprising a polar comonomer content greater than 0.4 wt.% Polymer composition of polyethylene copolymer
[0282] Two types of C=C containing functional groups were quantified in polyethylene copolymers with polar comonomer content greater than 0.4 wt%, each with a characteristic absorption and calibrated to different model compounds to give their own extinction coefficients:
[0283] Based on 1-decene [dec-1-ene], by 910 cm -1 The vinyl group (R-CH=CH2) gives E=13.13 L·mol -1 mm -1
[0284] Based on 2-methyl-1-heptene [2-methylhept-1-ene], by 888cm -1 The vinylene (RR'C=CH2) gives E=18.24L·mol -1 mm -1
[0285] EBA:
[0286] For ethylene butyl acrylate (EBA) systems, the -1 A linear baseline correction was performed.
[0287] EEA:
[0288] For ethylene ethyl acrylate (EEA) systems, the -1 A linear baseline correction was performed.
[0289] EMA:
[0290] For ethylene methyl acrylate (EMA) systems, the-1 A linear baseline correction was performed.
[0291] On the other hand, ASTM D3124-98 and ASTM D6248-98 methods also include procedures for determining the molar extinction coefficient. At least three 0.18 mol·L -1 of carbon disulfide (CS2) solution and the average value of the molar extinction coefficient was used.
[0292] The amount of vinyl groups originating from the polyunsaturated comonomer per 1000 carbon atoms is determined and calculated as follows:
[0293] The polymer to be analyzed and the reference polymer are produced on the same reactor, using essentially the same conditions, i.e. similar peak temperatures, pressures and production rates, but the only difference is that a polyunsaturated comonomer is added to the polymer to be analyzed and is not added to the reference polymer. As described herein, the total amount of vinyl in each polymer is determined by FT-IR measurement. It is then assumed that the baseline level of vinyl is the same for the reference polymer and the polymer to be analyzed, i.e., those vinyls formed by the method and by the chain transfer agent (if present) that produces vinyl, with the only exception that in the polymer to be analyzed, a polyunsaturated comonomer is also added to the reactor. This baseline level is then subtracted from the amount of vinyl measured in the polymer to be analyzed, thereby obtaining the amount of vinyl / 1000 carbon atoms, which is produced by the polyunsaturated comonomer.
[0294] Tanδ measurement on 10kV cables
[0295] Cable core production
[0296] A 10 kV cable core having the following dimensions (described below) was extruded and vulcanized on a CCV pilot cable production line equipped with a three-layer die head, with a production line speed of 5.76 m / min, a heating zone temperature setting of 490 / 415 / 395 / 375° C. in the vulcanizing tube, and then the cable core was cooled with water. The semiconductive layer used for the two 10 kV cable cores (insulation layer thickness of about 3.5 mm) comprised the same semiconductive material in both the inventive example and the comparative example.
[0297] The inner and outer semiconductive layers consist of LE0595 (containing carbon black and peroxide) supplied by Borealis. The cable core has the following dimensions:
[0298] 50mm 2 Aluminum conductor
[0299] Inner semi-conductive layer: thickness 1.0±0.1mm
[0300] Insulation layer: Thickness 3.5 to 3.6 mm
[0301] Outer semi-conductive layer: thickness 1.0±0.1mm
[0302] Adjustment processing:
[0303] Before the tan δ measurements were carried out, the cable cores were heat treated in a ventilated oven at 70° C. for 72 hours. After the conditioning treatment, the cable cores were stored at room temperature.
[0304] Cable core sample preparation and tan delta measurement:
[0305] The active part of the cable core is greater than 10m, usually between 10 and 15m. The ends of the cable core are water terminated in circulating deionized water. A protective ring is attached to each end of the insulation layer about 1cm away from the insulation screen in the water termination. The protective ring is grounded, and the last part of the insulation screen in the water termination is additionally covered by insulating tape to eliminate measurement errors of the termination.
[0306] The cable core is coiled in an oven for tan delta measurements. When the test is performed above room temperature, the active part of the cable core between the oven and the water termination (approximately 50 cm at each end) is surrounded by a metal tube with circulating air from the oven. In this way, the entire active part of the cable core up to the water termination is exposed to the same temperature.
[0307] The movable part is covered with aluminum foil.
[0308] To achieve a stable temperature, the cable core is heated in an oven for at least 1.5 hours to achieve an isothermal state. The cable core is therefore heated by the oven and not by the conductor.
[0309] The tan delta measurement is performed using a Tettex 2840 measuring bridge. The measurement for each voltage level is performed when the bridge shows a stable value, typically within 1 minute. In the example, the applied voltage level is adjusted to achieve the following conductor stresses: 5 kV / mm, 10 kV / mm and 15 kV / mm to determine the tan delta of the cable core at a temperature of 90 °C.
[0310] Salt water humidity aging test
[0311] Cable core production:
[0312] A 20 kV cable core having the following dimensions (described below) was extruded and vulcanized on a CCV pilot cable production line equipped with a three-layer die head at a line speed of 2.79 m / min, with the heating zone temperature in the vulcanizing tube set at 460 / 400 / 385 / 375° C., and then the cable core was cooled with water. The semiconductive layer used in the two 20 kV cables (insulation layer thickness of about 5.5 mm) contained the same semiconductive material in both the inventive example and the comparative example.
[0313] The inner and outer semiconductive layers consist of LE0595 (containing carbon black and peroxide) supplied by Borealis. The cable has the following dimensions:
[0314] 150mm 2 Aluminum conductor
[0315] Inner semi-conductive layer: thickness 1.0±0.1mm
[0316] Insulation layer: Thickness 5.5 to 5.6 mm
[0317] Outer semi-conductive layer: thickness 1.0±0.1mm
[0318] The wet aging characteristics of the cable core in salt water were evaluated using the Schedule A procedure described in Cigré Technical Manual 722 “Additional Test Recommendations for 6 kV (Um=7.2 kV) to 60 kV (Um=72.5 kV) Submarine Cables” published in April 2018.
[0319] Preprocessing:
[0320] The cable core was immersed in a water tank at a temperature of 55° C. for 500 hours. The NaCl content in the water was 3.5% by weight.
[0321] aging:
[0322] The cable core was subjected to electrical aging in a water tank. The water temperature was 40°C and the applied 50 Hz voltage was 50 kV, which was equivalent to a conductor stress of 12 kV / mm. The NaCl content in the water was 3.5 wt%.
[0323] AC breakdown test:
[0324] AC breakdown test is performed after 1 year of aging according to Cigré Technical Manual 722 Section 3.6.4.1 and HD 605 5.4.15.3.4 (b). The cable core is cut into six test specimens with an effective length of 10 meters (including terminations in addition). Within 72 hours after the specimen is removed from the aging tank, a 50Hz AC step test is performed to test its breakdown according to the following procedure:
[0325] Start at 36kV for 5 minutes
[0326] The voltage is increased in steps of 12 kV every 5 minutes until breakdown occurs
[0327] The calculation of the AC breakdown strength values and the Weibull parameters for the six breakdown value data sets followed the least squares regression procedure described in IEC 62539 (2007).
[0328] Experimental Section
[0329] The following materials are used in these examples:
[0330] EEA1 is a LDPE copolymer of ethylene and 15 wt% of ethyl acrylate comonomer (i.e. polar comonomer), produced by a high pressure process. MFR2 is about 7 g / 10 min.
[0331] LDPE1 is an LDPE copolymer of ethylene and 1,7-octadiene comonomer (ie, a polyunsaturated comonomer) having a vinyl content of about 0.50-0.55 vinyl groups / 1000 carbon atoms and an MFR2 of about 2 g / 10 min, produced by a high pressure process.
[0332] DCP: Dicumyl Peroxide
[0333] Preparation of insulating layer composition
[0334] The cable core of the present invention and the insulating layer composition used in the above-mentioned cable core preparation method have been prepared and compared, see Table 1 below. The antioxidant described herein is added to the polymer component of the insulating layer composition of the inventive example and the comparative example in the amount described herein, and an intermediate composition is formed by compounding and melt mixing, and then it is made into particles. The crosslinking agent (the crosslinking agent is in liquid form) is dispersed on the particles of the intermediate composition, thereby adding the crosslinking agent to these intermediate compositions. The wet particles are retained until the particles become dry. The amount of the crosslinking agent used to crosslink different compositions is shown in Table 1 below for the description of the insulating layer composition of the inventive example and the comparative example. The scorch retarder with CAS No. 6362-80-7 is added to the composition in a manner similar to the crosslinking agent.
[0335] Table 1 - Insulation compositions of inventive examples and comparative examples (wt%)
[0336] Composition Invention Example 1 Comparative Example 1 Component (ii) - EEA1 1.96 22.81 Component (i) - LDPE1 96.22 74.89 Antioxidant CAS (96-69-5) 0.12 0.20 Add the following components to the above composition Anti-scorch agent CAS 6362-80-7 0.35 0.40 DCP 1.35 1.70 Polar comonomer in insulating layer (μmol / g) 29.40 342.15
[0337] The dielectric loss of the inventive example and comparative example 1 was determined by tan δ measurements under different conductor stresses. Table 2 below summarizes the measured tan δ values.
[0338] It can be clearly seen that the dielectric loss of Inventive Example 1 is significantly lower than that of Comparative Example 1, which represents a conventional polymer WTR solution.
[0339] Table 2 - tan delta results measured on 10 kV cable samples with LE0595 as inner and outer semi-conductive layers
[0340]
[0341] As described above, the AC breakdown strength of the 20 kV cable comprising Inventive Example 1 was measured after 1 year of wet aging in salt water. In the test results after 1 year of AC breakdown test, the inventors believe that the use of the insulating composition according to the present invention has obvious benefits when performing wet aging test in a salt water environment.
[0342] In the cable insulated with the polymer composition of Inventive Example 1, the Weibull Eb (63.2%) value after 1 year of wet aging was 48.8 kV / mm. Assuming a design conductor stress of 8 kV / mm, the breakdown value meets the criteria described in CIGRE TB722. These results confirm the benefits of the composition according to the present invention, indicating that the composition is particularly suitable for use in salt water environments.
[0343] Table 3 below summarizes the measured Eb values and test conditions.
[0344] Table 3 - AC breakdown strength after 1 year of wet aging in salt water according to CIGRE TB722
[0345]
Claims
1. A submarine cable core comprising a conductor, the conductor being surrounded in sequence at least by an inner semiconducting layer, an insulating layer and an outer semiconducting layer; in, The insulating layer comprises: (i) a low density polyethylene homopolymer or a low density polyethylene copolymer comprising at least one polyunsaturated comonomer and optionally one or more other comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate, Wherein, based on the total amount of polymer in the insulating layer, the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram.
2. The submarine cable core according to claim 1, wherein at least one of the inner semiconductive layer and the outer semiconductive layer independently comprises: (a) a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate; and (b) Carbon black.
3. A submarine cable core according to claim 1 or 2, wherein the chemical composition of the inner semiconducting layer is the same as the chemical composition of the outer semiconducting layer.
4. A submarine cable core according to claims 2 to 3, wherein the inner semiconductive layer and / or the outer semiconductive layer comprises ethylene alkyl acrylate or ethylene vinyl acetate copolymer, preferably ethylene alkyl acrylate.
5. The submarine cable core according to claims 1 to 4, wherein component (ii) of the insulation layer is an ethylene alkyl acrylate copolymer.
6. The submarine cable core according to claim 5, wherein the ethylene alkyl acrylate copolymer is ethylene methyl acrylate, ethylene ethyl acrylate or ethylene butyl acrylate, preferably ethylene ethyl acrylate.
7. A submarine cable core according to claims 1 to 6, wherein the polyunsaturated comonomer of the low density polyethylene copolymer of component (i) is a straight carbon chain having at least 8 carbon atoms and at least 4 carbon atoms located between non-conjugated double bonds, wherein at least one double bond is located at the terminal.
8. The submarine cable core according to claims 1 to 7, wherein the polyunsaturated comonomer of the low density polyethylene copolymer of component (i) is C8 to C 14 The non-conjugated diene is preferably selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene, 1,13-tetradecadiene or a mixture thereof, and more preferably selected from 1,7-octadiene, 1,9-decadiene, 1,11-dodecadiene or 1,13-tetradecadiene.
9. Submarine cable core according to claims 1 to 8, wherein at least one of the insulation layer, the inner semiconducting layer and the outer semiconducting layer comprises a crosslinking agent, preferably a peroxide.
10. A submarine cable core according to claims 1 to 9, wherein the conductor comprises aluminium.
11. A submarine cable core according to claims 1 to 10, comprising a conductor, said conductor being surrounded in sequence at least by an inner semiconducting layer, an insulating layer and an outer semiconducting layer; in, The inner semiconductive layer and / or the outer semiconductive layer independently comprises, based on the total weight of each semiconductive layer: (a) at least 49.5 weight percent of a low density polyethylene copolymer comprising a polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates, and vinyl acetate; (b) 25 to 48 wt. % carbon black; and (c) 0.1 to 2.5 wt. % peroxide; and Wherein, based on the total weight of the insulating layer, the insulating layer comprises: (i) at least 88.0 wt. % of a low density polyethylene homopolymer or a low density polyethylene copolymer having at least one polyunsaturated comonomer and optionally one or more other comonomers; and (ii) 0.5 to 9.50 wt. % of a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate; (iii) 0.1 to 2.5% by weight of a peroxide; Wherein, based on the total amount of polymer in the insulating layer, the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram.
12. A crosslinked submarine cable core obtained by crosslinking a cable core according to claims 1 to 11.
13. A crosslinked submarine cable core according to claim 12, wherein (i) the dielectric loss measured by tan δ value at 90°C and 5 kV / mm when measured on a 10 kV cable as described in the "Determination Methods" section is at most 4.5·10 -4 , preferably at most 4·10 -4 , for example 3.5·10 -4 , even more preferably at most 3·10 -4 , for example 2.5·10 -4 , and / or a tan δ value of at most 12·10 at 90°C and 10 kV / mm -4 , preferably at most 10·10 -4 , for example 8.10 -4 , even more preferably at most 7.5·10 -4 , for example 6.5·10 -4 , and / or wherein (ii) the AC breakdown strength value after 1 year is at least 40 kV / mm, preferably at least 45 kV / mm, when measured on a 20 kV cable as described in the "Determination Methods" section.
14. Use of a submarine cable core according to any one of claims 1 to 11 or a crosslinked submarine cable core according to any one of claims 12 to 13 in a submarine cable in a saltwater environment such as in the sea or on the seabed, for example for transmitting electricity.
15. A submarine cable comprising at least one, preferably at least two, more preferably at least three submarine cable cores according to claims 1 to 14.
16. The submarine cable according to claim 15, which is a submarine AC cable system, preferably a submarine high voltage (HV) AC cable system.
17. A power generation system comprising: (A) offshore generators, such as wind turbines; (B) The submarine cable according to claim 15 or 16, which connects the offshore generator to a substation located offshore and / or on land via the sea or seabed.
18. Use of a low density polyethylene copolymer of ethylene and at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates or vinyl acetate in the insulation layer of a submarine cable, wherein: The amount of polar monomer units in the insulation layer is 1 to 150 micromoles per gram based on the total amount of polymer components in the insulation layer to minimize water tree degradation and dielectric loss measured by tan delta of a submarine cable core used for a submarine cable in a seawater environment such as in the sea or on the sea floor; The submarine cable core comprises a conductor, which is surrounded by at least an inner semiconducting layer, an insulating layer and an outer semiconducting layer in sequence; Wherein, the insulating layer comprises: The insulation layer contains: (i) a low density polyethylene homopolymer or a low density polyethylene copolymer comprising at least one polyunsaturated comonomer and optionally one or more other comonomers; and (ii) a copolymer comprising at least one polar comonomer selected from the group consisting of alkyl acrylates, alkyl methacrylates and vinyl acetate, Wherein, based on the total amount of polymer components in the insulating layer, the amount of polar monomer units in the insulating layer is 1 to 150 micromoles per gram.
Citation Information
Patent Citations
Process for producing carbon blacks and new carbon blacks
EP0629222A1
Polymer composition having improved wet ageing properties
EP1731566A1
Process and apparatus for the production of carbon black
US3401020A
Process for producing carbon black
US3922335A
Process for producing carbon black
US4340577A
Cited By
Insulating material, preparation method thereof and cable
CN119552312A